AL-‘ALAAQAH BAINA ITQAAN AL-MUFRADAAT WAL INSYAA` AT-THULLAAB AS-SHAF AT-TAASI’ FII AL-MADRASAH AT-TSANAWIYYAH MA’HAD UMMUL QURO AL-ISLAMI BOGOR - Roilah; Muh Abrar; Lukman Taufik Akasahtia (SHAWTUL ARAB, 2022)
Creating or composing is a writing activity directed at expressing main ideas in the form of ideas, messages, feelings, etc. in written language and not just visualizing shapes, letters, words or sentences. Create an article in Arabic. Students can write if they master the vocabulary. Because vocabulary is the most important thing a person needs in a language. Therefore, vocabulary has a very important role in the ability to speak Arabic. The more a person masters the vocabulary, the smarter the person is at expressing thoughts or ideas in Arabic writing. This research aims to determine the relationship between vocabulary mastery and composition in Umm Qara Islamic School Bogor. Thus, it can be concluded that there is a positive relationship between vocabulary mastery and composition